Effect of Lemon Peel Extract Concentration on Nano Scale Fe/Fe3O4 Synthesis - Aydogan, Tugce; Dumanli, F. Tugce Senberber; Derun, Emek Moroydor (GAZI UNIV, 2022)
Iron nanoparticles has attracted more attention than other nanomaterials for its small particle size, high magnetism, low toxicity, surface properties and its extensive applications in science. Plant extracts, microorganisms and agricultural waste products are used for the green synthesis of these nanoparticles. Green synthesis uses metabolites obtained from plants and microorganisms as reducing and covering agents. In addition, it provides an advantage over other synthesis methods because it does not contain harsh chemicals, uses non-toxic reagents, is biocompatible and environmentally friendly. In this study, iron-iron oxide (Fe-Fe3O4) nanoparticles (LP- Fe NPs) were synthesized using lemon peel extract and optimum Fe:Lemon peel extract (Fe: LP exract) ratio was determined. Nanoparticles were characterized by X-ray diffractometer (XRD), UV-vis Spectrophotometer and Scanning Electron Microscope (SEM). The UV-vis absorption spectrum of iron nanoparticles showed a peak in the 250-350 nm range. XRD analysis results confirmed that the product is a Fe-Fe3O4 mixture. According to SEM analysis results, the largest particle size according to the 1:2 ratio was recorded as 159 nm. The smallest particle size was recorded as 66.68 nm. It has been observed that the increased lemon peel extract causes agglomeration. As a result, green synthesis of lemon peel, which is agricultural waste; It creates low-cost, environmentally friendly products.
Keywords: Green synthesis; morphology; nanomaterial; iron nanoparticle; lemon peel; NANOPARTICLES; AGENT; Engineering